2022
DOI: 10.3389/fpls.2022.862875
|View full text |Cite
|
Sign up to set email alerts
|

Safety Level of Microorganism-Bearing Products Applied in Soil-Plant Systems

Abstract: The indiscriminate use of chemical fertilizers adversely affects ecological health and soil microbiota provoking loss of soil fertility and greater pathogen and pest presence in soil-plant systems, which further reduce the quality of food and human health. Therefore, the sustainability, circular economy, environmental safety of agricultural production, and health concerns made possible the practical realization of eco-friendly biotechnological approaches like organic matter amendments, biofertilizers, biopesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Most studies have been conducted with bacteria; however, although they are the main decomposers of organic matter and dictate soil carbon and other elements, the role of fungi is the subject of relatively few studies. Many fungi can solubilize insoluble phosphates or facilitate P acquisition by plants; and therefore, they form an important part of commercial microbial products, with Aspergillus, Penicillium, and Trichoderma being the most efficient [73].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have been conducted with bacteria; however, although they are the main decomposers of organic matter and dictate soil carbon and other elements, the role of fungi is the subject of relatively few studies. Many fungi can solubilize insoluble phosphates or facilitate P acquisition by plants; and therefore, they form an important part of commercial microbial products, with Aspergillus, Penicillium, and Trichoderma being the most efficient [73].…”
Section: Discussionmentioning
confidence: 99%
“…This diversity of variables means that one approach for the production and application of fungal P-solubilizers cannot fit all the different contexts, but that different and interconnected strategies should be investigated (Figure 2). Based on the scientific literature, a strong wave of novel strategies and wider application of fungal biofertilizers are expected in the near future including in the field of fungal P-solubilization, always looking for safe and healthy final products [106,107].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of soils biodiversity and health affects the quality and quantity of yields. We are aware, confirmed by numerous scientific studies, that the value of the soil is primarily determined by its biocomponents, including microbiota currently considered one of the most important factors in the health of the soil and the plants grown in it (Vassileva et al, 2022). It is indicated that the potential threats to microorganisms caused by NPs include, among others, their removal from the rhizosphere, disturbance of important biological functions, such as nitrogen fixation, phosphate solubilisation, potassium uptake, nodulation and hormone synthesis (Ameen et al, 2021).…”
Section: Introductionmentioning
confidence: 96%